(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The article describes the development of the medical field in the region during the 1950s-1960s, the issue of staffing in the organization of the healthcare system, and the participation of female doctors in this process. Additionally, it provides information on the role of female doctors in protecting public health, their involvement in medical services, and their contributions to the further development of medicine in Surkhandarya.